2016
DOI: 10.14423/smj.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Does Alkaline Colonic pH Predispose to Clostridium difficile Infection?

Abstract: A strong association between C. difficile infection and alkaline stool pH was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…SCFAs are produced from dietary and hostderived carbohydrates, mainly by Lachnospiraceae and Ruminococcaceae, the families that were less abundant in CDI patients and carriers. They may have an effect on colonization resistance through reducing the luminal pH (and thereby creating an unfavorable environment for C. difficile) (44) and stimulating the defensive barrier, as one of the SCFAs (butyrate) is the main energy source of the gut epithelium (45,46). Amino acids may also play a role in susceptibility to C. difficile colonization, as they can enhance germination in the presence of secondary bile acids and may influence the immune system.…”
Section: Roles Of the Microbiotamentioning
confidence: 99%
“…SCFAs are produced from dietary and hostderived carbohydrates, mainly by Lachnospiraceae and Ruminococcaceae, the families that were less abundant in CDI patients and carriers. They may have an effect on colonization resistance through reducing the luminal pH (and thereby creating an unfavorable environment for C. difficile) (44) and stimulating the defensive barrier, as one of the SCFAs (butyrate) is the main energy source of the gut epithelium (45,46). Amino acids may also play a role in susceptibility to C. difficile colonization, as they can enhance germination in the presence of secondary bile acids and may influence the immune system.…”
Section: Roles Of the Microbiotamentioning
confidence: 99%
“…One possible mechanism for regulation of C. difficile susceptibility by SCFA is modulation of luminal pH. When concentrations of SCFAs decline, pH increases, resulting in an environment that is favorable for growth of Enterobacteriaceae and Clostridia, including C. difficile (103105). …”
Section: Carbohydrate Fermentationmentioning
confidence: 99%
“…The loss of function of NHE3 by toxin B of C. difficile caused an altered intestinal environment with an increase in the luminal and fecal pH (23). A further cohort study reported a strong association between a more alkaline fecal pH and CDI, suggesting that higher pH in the GI tract may influence disease symptoms (24).…”
Section: Introductionmentioning
confidence: 99%